Catechol‐O‐Methyltransferase Genotype, Frailty, and Gait Speed in a Biracial Cohort of Older Adults. Issue 2 (12th October 2020) - Mance, Shannon; Rosso, Andrea; Bis, Joshua; Studenski, Stephanie; Bohnen, Nico; Rosano, Caterina
Abstract : OBJECTIVE: To examine whether the association between dopamine‐related genotype and gait speed differs according to frailty status or race. DESIGN: Cross‐sectional population‐based study (Cardiovascular Health Study). SETTING: Multicenter study, four U.S. sites. PARTICIPANTS: Volunteer community‐dwelling adults aged 65 years and older, without evidence of Parkinsonʼs disease (N = 3, 744; 71 years; 82% White; 39% male). MEASUREMENTS: Gait speed (usual pace; m/s), physical frailty (Fried definition), and genetic polymorphism of catechol‐O‐methyltransferase ( COMT ; rs4680), an enzyme regulating tonic brain dopamine levels, were assessed. Interaction of COMT by frailty and by race predicting gait speed were tested, and, if significant, analyses were stratified. Multivariable regression models of COMT predicting gait speed were adjusted for demographics and locomotor risk factors. Sensitivity analyses were repeated, stratified by clinical cutoffs of gait speed (0.6 and 1.0 m/s) instead of frailty status. RESULTS: The interaction of COMT by frailty and COMT by race were P = .02 and P = .01, respectively. Compared with Met/Met (higher dopaminergic signaling), the Val/Val group (lower dopaminergic signaling) walked marginally more slowly in the full cohort (0.87 vs 0.89 m/s; P = .2). Gait speed differences were significant for frail (n = 220; 0.55 vs 0.63 m/s; P = .03), but not for prefrail (n = 1, 691; 0.81 vs 0.81 m/s; P = .9) or nonfrail (n = 1, 833; 0.98 vs 0.97 m/s; P = .7); results were similar in fully adjusted models. Among frail, associations were similar for Whites and Blacks, with statistical significance for Whites only. Associations stratified by clinical cutoffs of gait speed were not significant. CONCLUSION: The association of dopamine‐related genotype with gait speed is stronger among adults with frailty compared with those without frailty. The potential effects of dopaminergic signaling on preserving physical function in biracial cohorts of frail adults should be further examined.